Peran Kuliah Kerja Nyata dalam Penguatan Moderasi Beragama di Tingkat Desa: Analisis Pengalaman Mahasiswa UINSU di Desa Susuk, Kecamatan Tiganderket, Kabupaten Karo - Muhammad Mitra; Sahan Irvando; Muhammad Hasbi Maulana; Zahrani Fatni Hapsah; Diva Viola Natasya Hasibuan; Ade Widya; Siti Ardianti (BADAN PENERBIT STIEPARI PRESS, 2025)
This study explores the implementation of religious moderation through the Community Service Program (KKN) by UINSU students in Susuk Village, Tiganderket Subdistrict, Karo Regency. Religious moderation is seen as a strategic response to radicalism, intolerance, and exclusivism, particularly in rural areas with limited access to religious literacy. Using a qualitative case study with a constructivist paradigm, data were collected through observation, in-depth interviews, and documentation. The analysis employed the Miles and Huberman model with triangulation of sources, methods, and time. Findings show that religious moderation was implemented through educational, religious, and social activities, such as teaching, literacy promotion, anti-bullying campaigns, Quranic recitation, religious study groups (wirid), health services (posyandu), and MSME empowerment. Key supporters included village officials, religious leaders, schools, and community members. Challenges included limited facilities, short program duration, and differing community perceptions of moderation. The KKN program significantly impacted students by enhancing social competence and practical understanding of religious moderation, while also fostering tolerance, moderate religious education, and social cohesion in the community. This demonstrates that KKN is an effective tool for promoting wasathiyah Islamic values at the grassroots level.